Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1088/1361-665x/ab6026
|View full text |Cite
|
Sign up to set email alerts
|

Improving the damping behavior of fiber-reinforced polymer composites with embedded superelastic shape memory alloys (SMA)

Abstract: One-way shape memory alloy wires exhibiting super elastic properties are capable of generating high recovery stresses under constrained conditions upon external mechanical loading. In the present work, the damping response of hybrid composite materials enhanced with super-elastic NiTi alloy wires is examined. The studied system consisted of an aramid reinforced epoxy resin composite in which NiTi wires have been embedded. By conducting damping measurements it was found that the addition of Ni-Ti wires into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…DMA was employed to investigate the composites' storage modulus, loss modulus, and damping factor as a function of temperature and frequency. Katsiropoulus et al have studied the damping behavior of fiber-reinforced polymer composites using DMA [12]. They analyzed the effect of fiber type, fiber orientation, and matrix properties on the storage modulus, loss modulus, and damping factor.…”
Section: Introductionmentioning
confidence: 99%
“…DMA was employed to investigate the composites' storage modulus, loss modulus, and damping factor as a function of temperature and frequency. Katsiropoulus et al have studied the damping behavior of fiber-reinforced polymer composites using DMA [12]. They analyzed the effect of fiber type, fiber orientation, and matrix properties on the storage modulus, loss modulus, and damping factor.…”
Section: Introductionmentioning
confidence: 99%
“…Under static loading condition, up to 4 wt% of shape memory alloy reinforcement, the GFRP exhibit enhanced flexure resistance. Katsiropoulos et al [ 21 ] improved the damping behavior of fiber reinforced polymer composites with embedded superelastic SMA. It was found that the addition of Ni-Ti wires into the aramid/epoxy composite leads to a significant modification of its damping, which depends strongly on wire volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is great interest in portable lightweight devices, where actuation is based on shape memory alloys (SMA). Additionally, SMAs can be embedded in a polymeric matrix to gain actuation capabilities [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%